Pengaruh Iklim Organisasi Dimediasi Work Engagement terhadap Kinerja Karyawan PT Ciriajasa Cipta Mandiri Jakarta Selatan - Andini, Narendraputri; Yunita, Tyna; Jumawan, Jumawan; Silalahi, Edward; Sumantyo, Franciscus Dwikotjo Sri (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
The Influence of Organizational Climate Mediated by Work Engagement on Employee Performance at PT. Ciriajasa Cipta Mandiri. This research aims to find out whether Organizational Climate can influence the performance of Work Engagement mediation found in Employee Performance at PT Ciriajasa Cipta Mandiri. With quantitative research methods, the population and sample are saturated. The sample used in this research was 205 respondents. The results of this research explain that organizational climate variables have a positive and significant effect on Work Engagement. Because Organizational Climate has a value of (T statistics 21.565 > T table 1.65) and (P Value 0.000 < 0.05). So the direct influence of the Organizational Climate variable on Work Engagement is proven to be significant and stated to be full. The organizational climate variable has a negative effect on job satisfaction. The Work Engagement variable has a positive and significant effect on employee performance. The researcher realizes that this research has shortcomings and limitations, however, the researcher hopes that this research can be useful for the parties involved in this research. This research can be used to expand knowledge and complete the literature regarding the Influence of Organizational Climate Mediated by Work Engagement as an Intervening Variable in PT. Ciriajasa Cipta Mandiri.